Intention to Use Prophetic Medicine as Halal Therapeutics in Indonesia; An Extended TPB Approach - Dita Pratiwi Kusumaningtyas; Dian Friantoro; Zahra Suci Ramadhani; Illiyyun Illiyyun; Ashada Laili Rohmah; Gefira Aulannisa (JESI (Jurnal Ekonomi Syariah Indonesia), 2026)
Purpose: Prophetic medicine (Thibbun Nabawi) is a health practice derived from the teachings of the Prophet Muhammad, including cupping therapy (hijama), ruqyah, and halal herbal remedies. Despite its potential within the halal therapeutics industry, its utilization in Indonesia remains relatively low and not fully aligned with the growing awareness of halal lifestyle. This study aims to analyze the factors influencing Indonesian society’s intention to use prophetic medicine by developing an extended Theory of Planned Behavior (TPB) framework incorporating religiosity, halal knowledge, and health consciousness. Methodology: This study employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected from 467 Muslim respondents across various provinces in Indonesia to test the proposed model Results: The findings indicate that religiosity, halal knowledge, and health consciousness significantly influence attitudes toward prophetic medicine. Attitude, subjective norms, and perceived behavioral control significantly predict intention to use prophetic medicine. Mediation analysis confirms that attitude mediates the effects of religiosity, halal knowledge, and health consciousness on behavioral intention. Conclusion: The extended TPB model effectively explains Muslim consumers’ intention to use prophetic medicine, with attitude playing a central role. Implications: Stakeholders should promote halal therapeutics by strengthening attitudes through religious values, halal knowledge, and health-oriented communication. Originality: This study extends TPB by integrating religiosity, halal knowledge, and health consciousness in the underexplored context of prophetic medicine.